Computational study of a single-phase flow in packed beds of spheres - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
Packed-bed reactors are widely used in petrochemical, fine chemical, and pharmaceutical industries. Detailed knowledge of interstitial flow in the void space of such packed-bed reactors is essential for understanding the heat and mass transfer characteristics. In this paper, fluid flow through the array of spheres was studied using the unit-cell approach, in which different periodically repeating arrangements of particles such as simple cubical, 1-D rhombohedral, 3-D rhombohedral, and face-centered cubical geometries were considered. Single-phase flow through these geometries was simulated using computational fluid dynamics (CFD). The model was first validated by comparing predicted results with published experimental and computational results. The validated model was further used to study the effect of particle arrangement/orientation on velocity distribution and heat transfer characteristics. The simulated results were also used to understand and to quantify, relative contributions of surface drag and form drag in overall resistance to the flow through packed-bed reactors. The model and the results presented here would be useful in elucidating the role of microscopic flow structure on mixing and other transport processes occurring in packed-bed reactors. (C) 2005 American Institute of Chemical Engineers.
Keywords: CFD; drag; heat transfer; packed bed; packing arrangement

Dynamics of drop impact on solid surface: experiments and VOF simulations - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
The process of spreading/recoiling of a liquid drop after collision with a flat solid surface was experimentally, and computationally studied to identify the key issues in spreading of a liquid drop oil a solid surface. The long-term objective of this study is to gain an insight in the phenomenon of wetting of solid particles in the trickle-bed reactors. Interaction of a falling liquid drop with a solid surface (impact, spreading, recoiling, and bouncing) was studied using a high-speed digital camera. Experimental data oil dynamics of a drop impact on flat surfaces (glass and Teflon) are reported over a range of Reynolds numbers (550-2500) and Weber numbers (2-20). A computational fluid dynamics (CFD) model, based on the volume of fluid (VOF) approach, was used to simulate drop dynamics on the flat sufaces. The experimental results were compared with the CFD simulations. Simulations showed reasonably good agreement with the experimental data. A VOF-based computational model was able to capture key features of the interaction of a liquid drop with solid surfaces. The CFD simulations provide information about finer details of drop interaction with the solid surface. Information about gas-liquid and liquid-solid drag obtained from VOF simulations would be useful for CFD modeling of trickle-bed reactors. (C) 2004 American Institute of Chemical Engineers.
Keywords: CFD; drop impact; recoiling; spreading; trickle bed; VOF

Gas-liquid flow generated by a Rushton turbine in stirred vessel: CARPT/CT measurements and CFD simulations - Khopkar, A. R.; Rammohan, A. R.; Ranade, V. V.; Dudukovic, M. P. (Chemical Engineering Science, 2005)
In this work, computer-automated radioactive particle tracking (CARPT), computed tomography (CT) and computational fluid dynamic (CFD) based models were used to investigate gas-liquid flow generated by a Rushton turbine. CARPT and CT measurements were carried out in a gas-liquid stirred vessel operating in two different flow regimes and captured the quantitative Eulerian information of gas-liquid flow. The CARPT data was then used to extract the circulation tune distribution in a vessel. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence (along the lines proposed by Brucato et al. (Chem. Eng. Sci. 45(1998) 3295)) were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). Most model predictions compared favourably with CARPT and CT measurements. Validated CFD models as attempted in this paper are promising to simulation of industrial stirred vessels. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CARPT; CFD; CT; gas-liquid flow; stirred vessel

CFD simulation of mixing in tall gas-liquid stirred vessel: role of local flow patterns - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Chemical Engineering Science, 2006)
In this work, we have used the computational fluid dynamics (CFD)-based models to investigate the gas-liquid flows generated by three down-pumping pitched blade turbines. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence [Khopkar and Ranade, 2005. CFD simulation of gas-liquid flow in a stirred vessel: VC, S33 and L33 flow regimes. A.I.Ch.E. Journal, accepted for publication] were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). The computational model has successfully captured the flow regimes as observed during experiments. The particle trajectory simulations were then carried out to examine the influence of the different flow regimes on the circulation time distribution. The model predictions were verified by comparing the predicted results with the experimental data of [Shewale and Pandit, 2006. Studies in multiple impeller agitated gas-liquid contactors. Chemical Engineering Science 61, 489-504]. The computational model and results discussed in this study would be useful for explaining the implications local flow patterns on the mixing process and extending the applications of CFD models for Simulating large multiphase stirred reactors. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CFD; Flow regimes; mixing; pitched blade turbine; stirred vessel

CFD simulation of shortstopping runaway reactions in vessels agitated with impellers and jets - Dakshinamoorthy, D.; Khopkar, A. R.; Louvar, J. F.; Ranade, V. V. (Journal of Loss Prevention in the Process Industries, 2006)
Runaway reactions are continuing to be a problem in the chemical industry. A recent study showed that 26% of our major chemical plant accidents are due to runaways. The consequences of runaway reactions are usually mitigated with (a) reliefs and containment systems or (b) shortstopping (reaction inhibition). This study covers the concept of shortstopping. One of the major reasons for runaways is power failure. In the advent of a power failure, mixing an inhibiting agent with the reactor contents is challenging. However, jets or impellers driven by a small generator can be used for mixing. This study compares shortstopping results in vessels agitated with jets and impellers using computational fluid dynamics (CFD). A commercial CFD code, Fluent is used. For shortstopping systems relying on jet mixing, angle and diameter of jet nozzle and jet velocity are the key design/operating parameters. For the systems with impellers, type, size and RPM of impeller are the key parameters. In this work, mixing with a jet mixer is first investigated for three nozzle diameters and two angles of injection. The best jet mixer configuration on the basis of mixing time is used for shortstopping studies. The simulated shortstopping results with the jet mixer are then compared with those obtained with impeller (Rushton and pitched blade turbine) stirred vessels. Our results identify the conditions for effective shortstopping; i.e., agitation requirements, locations for adding the inhibitor, and the quantity of inhibitor. The distribution of excess inhibitor is shown to be an important and essential design criterion for effective shortstopping when using impeller stirred vessels. The comparative study with a single jet shows that jet mixer is ineffective when used for shortstopping. Efforts such as adding excess inhibitor and inhibition with higher reaction rates at the same power, proved to be ineffective when using jet mixer compared to the results with impellers. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; impeller stirred vessels; jet mixer; runaway reaction; shortstopping

Comparison of flow structures in spacer-filled flat and annular channels - Ranade, Vivek V.; Kumar, Anil (Desalination, 2006)
Spacers are designed to create directional changes in the flow through membrane modules. Such secondary flow structures reduce concentration polarization and membrane fouling. Obviously, type of the spacer used in membrane modules strongly influences the resulting flow and therefore performance of the module. In this work, we have modeled detailed fluid dynamics of spacer filled channels by using the `unit cell' approach. The validated computational fluid dynamics (CFD) model was used to evaluate performance of certain spacer shapes and compare the resulting fluid dynamics in flat and curved channels. The simulations show that fluid flow behavior in a spacer-filled flat and a spiral channel was not significantly different. This means that pressure drops and mass transfer coefficients measured in flat channels may provide adequate guidelines, which would also be valid for spiral-wound modules. The results presented in this work will have significant implications for identifying improved spacers with higher propensities to reduce fouling in membrane modules.
Keywords: annular channel; CFD; flat channel; membrane spacers

Eulerian-lagrangian simulations of unsteady gas-liquid flows in bubble columns - Buwa, Vivek V.; Deo, Dhanannjay S.; Ranade, Vivek V. (International Journal of Multiphase Flow, 2006)
We studied the dynamics of gas-liquid flows in a rectangular bubble column using Eulerian-Lagrangian simulations. Three-dimensional, unsteady simulations were performed to simulate the dynamic characteristics of the oscillating bubble plume. The effect of superficial gas velocity and aerated liquid height-to-column width (HI K) ratio on the dynamic and time-averaged flow properties was studied and the simulated results were validated using wall pressure and voidage fluctuation measurements. The effect of lift force and numerical diffusion on the dynamic and time-averaged properties is discussed in detail. Further, the results obtained using the Eulerian-Lagrangian simulations were compared with the Eulerian-Eulerian simulations. The bubble scale information, which is otherwise lost in the Eulerian-Eulerian simulations, was validated using the voidage fluctuation measurements. Such experimentally validated Eulerian-Lagrangian models will be useful for the simulation of mass transfer and reactions in bubble columns. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Bubble column; CFD; Dynamics; Eulerian-Eulerian simulations; Eulerian-Lagrangian simulations; gas-liquid flow

Modeling of bubble column slurry reactor for reductive alkylation of p-phenylenediamine - Chaudhari, Amit S.; Rampure, Mohan R.; Ranade, Vivek V.; Jaganathan, Rengaswamy; Chaudhari, Raghunath V. (Chemical Engineering Science, 2007)
A bubble column slurry reactor (BCSR) model has been developed for the reductive alkylation of p-phenylenediamine (PPDA) with methyl ethyl ketone (MEK) to N, N'-di-secondary-alkyl-p-phenylenediamine (Di-amine). This particular reaction system is commercially relevant and involves a combination of parallel and consecutive reactions comprising equilibrium non-catalytic (homogeneous) and catalytic (heterogeneous) steps. The proposed model is based on the `mixing cell approach'. In this work the mixing cell approach has been extended by including a liquid backflow stream from all but the bottommost mixing cell. The model incorporates the contributions of gas-liquid and liquid-solid mass transfer, heat effects, and complex multistep reaction kinetics. CFD model is used to estimate the extent of backflow among mixing cells and its dependence on operating parameters. The effect of gas and liquid velocities, catalyst loading, inlet PPDA concentration, and temperature on the conversion, selectivity, global rate of hydrogenation, and temperature rise is discussed. The comparison of the current approach with the traditional mixing cell model is discussed. The BCSR model presented here will be useful to provide guidelines for designing and improving overall performance of bubble column reactors. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: bubble columns; CFD; kinetics; Mathematical modeling; Reductive alkylation

Singlejet fluidized beds: experiments and CFD simulations with glass and polypropylene particles - Utikar, Ranjeet P.; Ranade, Vivek V. (Chemical Engineering Science, 2007)
Understanding hydrodynamics of bubbling fluidized beds is crucial in proper design and scale up of these beds. CFD models have shown promise in gaining this understanding. In order to generate confidence in CFD models, predicted time averaged and dynamical characteristics of the bubbling fluidized beds need to be validated against experimental data. This paper describes such studies with rectangular fluidized beds operated with a central jet. Digital image analysis and analysis of wall pressure fluctuations were used for this characterization. Fluidization of two types of particles, glass and polypropylene (PP) was studied at two different initial bed heights of H/D = 1 and 2 with three central jet velocities 5, 10 and 20 m/s. Time averaged as well as dynamical characteristics were studied. The Eulerian-Eulerian two fluid model based on kinetic theory of granular flows was used to simulate these experiments. The predicted results were compared with the experimental data and previously published correlations. Although, there is agreement with experimental data in some aspects, complete agreement was not found. The presented experimental data and comparison with CFD predictions will provide useful basis for further work on understanding bubbling fluidized beds. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; fluidized beds; hydrodynamics; image analysis; pressure fluctuations; single jet

Synthesis, structure, and reactivity of diazoketiminato complexes of platinum(II) and palladium(II): cytotoxic properties of a platinum complex - Pratihar, Jahar Lal; Shee, Biswaranjan; Pattanayak, Poulami; Patra, Debprasad; Bhattacharyya, Arindam; Puranik, Vedavati G.; Hung, C. H.; Chattopadhyay, Surajit (European Journal of Inorganic Chemistry, 2007)
{Reaction of the 2-(arylazo)anilines Ar-N = N-C6H4NH2 [
Keywords: CFD; hydro processing; scale-down; scale-up; trickle bed

CFD modeling of rotary cement kilns - Mujumdar, Kaustubh S.; Ranade, Vivek V. (Asia-Pacific Journal of Chemical Engineering, 2008)
Rotary cement kilns are widely used to convert calcineous raw meal into cement clinker, and are key components in the cement industry. In this article, we report a comprehensive computational fluid dynamics (CFD)-based model to capture key transport processes in rotary cement kilns. Separate but coupled computational models were developed for the bed and the freeboard regions of the rotary kiln. The complex swirling airflow produced by kiln burners, coal combustion, gas-phase combustion of volatile matter and radiative heat transfer in the freeboard region were modeled. The clinkerization reactions in the bed region were modeled assuming solids as pseudo fluids. Coating formation in cement kilns (for both bed and freeboard regions) was considered. Appropriate source and sink terms were developed to model transfer of CO(2) from the bed to the freeboard region due to calcination reaction in the bed region. The developed bed and freeboard models were coupled by mass and energy communication through common interface. These coupled computational models were able to quite satisfactorily predict the available data from industrial kilns and previously published results. The computational models were also able to capture the intricacies of the burning zones of rotary cement kilns for changing burner-operational parameters like axial to swirl ratio and oxygen enrichment. The developed approach, computational models and simulation results will not only help in developing better understanding of cement kilns but also provide quantitative information about influence of burner design and other design parameters on kiln performance. (C) 2008 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: burner; CFD; coal combustion; rotary cement kiln

CFD simulation of liquid-phase mixing in solid-liquid stirred reactor - Kasat, Gopal R.; Khopkar, A. R.; Ranade, V. V.; Pandita, A. B. (Chemical Engineering Science, 2008)
A comprehensive CFD model was developed to gain an insight into solid suspension and its implications on the liquid-phase mixing process in a solid-liquid stirred reactor. The turbulent solid-liquid flow in a stirred reactor was simulated using a two-fluid model with the standard k-epsilon. turbulence model with mixture properties. The multiple reference frames (MRFs) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model with necessary sub-models was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc., USA). The predicted solid concentration distribution was compared with the experimental data of Yamazaki et al. [ 1986. Concentration profiles of solids suspended in a stirred tank. Powder Technology 48, 205-216]. The computational model was then further extended to simulate and understand the implications of the suspension quality on liquid-phase mixing process. The computational model and the predicted results discussed here will be useful for understanding the liquid-phase mixing process in stirred slurry reactors in various stages of solid suspension. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: CFD; mixing; solid suspension; stirred reactor

Flow pattern in vortex diode: experiments and CFD simulations - Kulkarni, Amol A.; Ranade, V. V.; Rajeev, R.; Koganti, S. B. (AICHE Journal, 2008)
Vortex diodes are used as leaky nonreturn valves in applications, where it is desirable to avoid valves with moving parts. Despite their use in practice for several decades, no detailed analysis of the flow inside the vortex diodes is available. A strategy was derived for the CFD simulations of the vortical flow in diodes. A good agreement was seen between pressure drop (Delta P) across the inlet-outlet ports from CFD simulations, and the experimental data for five diode sizes. The simulations showed that in the reverse flow situation tangential velocity was dominant and resulted in conservation of angular momentum in the chamber until it reaches the axial exit port. This vortical motion induced a significant pressure drop (Delta P-r). The axial velocity gradient over the chamber cross-section helps in inducing relaminarization of the flow. In the forward flow mode, the fluid gets distributed radially over the chamber and exits through the tangential port, yielding low Delta P-f. The analysis showed that the performance of a diode is strongly affected by diode geometry, size, aspect ratio, nozzle configuration and Reynolds number. Among different configurations, the nozzles with entry port size equal to diode yielded higher diodicity. Simulations showed that using angle of divergence for diffuser sections of nozzles of the order of 7 degrees exhibited higher diodicity than smaller angles. It was also observed that at higher flow rates significantly higher diodicity was obtained using axial nozzles with larger radius of curvature for expander section. The modeling methodology and results presented will be useful for evolving better designs of vortex diodes.
Keywords: CFD; Diodicity; pressure drop; relaminarization; Vortex diode

Hysteresis in cloud heights during solid suspension in stirred tank reactor: experiments and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Aiche Journal, 2010)
Solid suspension in stirred tank reactor is widely used in process industries for catalytic reactions, dissolution of solids, crystallization, and so on. Suspension quality is a key issue in design and operation of stirred reactor and its determination is not straight forward. Cloud height measurements of solid suspension provide a relatively simple way to quantify quality of suspension. In this work, experiments were carried out to quantify variation of cloud heights with impeller speed and particle characteristics. These measurements were carried out using visual observations, image analysis, and ultrasound velocity profiler techniques. The obtained data demonstrated the existence of hysteresis in cloud heights with respect to impeller speed. Apart from possible applications in reducing power required for achieving desired solid suspension quality, the existence of hysteresis also provides a new way to evaluate computational fluid dynamics (CFD) simulations of solid liquid flows in stirred vessels. An attempt was made to capture observed hysteresis in cloud heights in CFD simulations. The simulated results were compared with the experimental data. The presented models and results (experimental and computational) will he useful for simulating complex solid liquid flows in stirred reactors. (C) 2010 American Institute of Chemical Engineers AIChE J, 56: 2795-2804, 2010
Keywords: CFD; hysteresis in cloud height; solid velocity profiles

CFD simulation of stirred tanks: comparison of turbulence models. part I: radial flow impellers - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
A critical review of the published literature regarding the computational fluid dynamics (CFD) modelling of single-phase turbulent flow in stirred tank reactors is presented. In this part of review, CFD simulations of radial flow impellers (mainly disc turbine (DT)) in a fully baffled vessel operating in a turbulent regime have been presented. Simulated results obtained with different impeller modelling approaches (impeller boundary condition, multiple reference frame, computational snap shot and the sliding mesh approaches) and different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model (RSM) and large eddy simulation) have been compared with the in-house laser Doppler anemometry (LDA) experimental data. In addition, recently proposed modifications to the standard k-epsilon models were also evaluated. The model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. A discussion is presented to highlight strengths and weaknesses of currently used CFD models. A preliminary analysis of sensitivity of modelling assumptions in the k-epsilon models and RSM has been carried out using LES database. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-epsilon model as well as RSM. The volume integral of predicted energy dissipation rate is compared with the energy input rate. Based on these results, suggestions have been made for the future work in this area.
Keywords: CFD; impeller models; k-epsilon models; LES; radial flow impellers; RSM; stirred vessel

CFD simulation of stirred tanks: comparison of turbulence models (Part II: axial flow impellers, multiple impellers and multiphase dispersions) - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
In the first part of the review, published literature regarding the CFD modelling of single-phase turbulent flow in stirred tank reactors with radial flow impellers was critically analysed. A brief overview of different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model and large eddy simulation) as well as impeller baffle interaction models has been presented in the previous part. This part is concerned with the review of literature regarding CFD simulation of axial flow impellers. Comprehensive simulations have been carried out using various turbulence models and the model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. The strengths and weaknesses of various turbulence models for axial flow impellers is presented. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-e model as well as Reynolds stress model. Literature efforts on multiple impeller systems and multiphase systems have been discussed in a separate section. Based on these results, suggestions have been made for the future work in this area.
Keywords: axial flow impellers; CFD; impeller models; stirred vessel; turbulence models

Scaling laws for gas-solid riser flow through two-fluid model simulation - Naren, P. R.; Ranade, Vivek. V. (Particuology, 2011)
Scale up of gas-solid circulating fluidized bed (CFB) risers poses many challenges to researchers. In this paper, CFD investigation of hydrodynamic scaling laws for gas-solid riser flow was attempted on the basis of two-fluid model simulations, in particular, the recently developed empirical scaling law of Qi, Zhu, and Huang (2008). A 3D computational model with periodic boundaries was used to perform numerical experiments and to study the effect of various system and operating parameters in hydrodynamic scaling of riser flow. The Qi scaling ratio was found to ensure similarity in global parameters like overall cross-sectional average solid holdup or pressure drop gradient. However, similarity in local flow profiles was not observed for all the test cases. The present work also highlighted the significance of error bars in reporting experimental values. (C) 2010 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences. Published by Elsevier B.V. All rights reserved.
Keywords: CFD; Error bar; Periodic boundary; Risers; Scaling; Two-fluid model

Solid suspension in stirred tanks: UVP measurements and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
Suspension of solids in stirred reactor is widely used for catalytic reactions, dissolution, etc. Quality of solid suspension is an important parameter required for the reliable design, optimum performance, and scale up of the system. Quality of suspension depends on local characteristics of solid velocity and hold up profiles. The present work was focused on investigating quality of solid suspension using ultrasound velocity profiler (UVP) measurements and CFD simulations. The slip velocity measurements carried out with UVP were used to evaluate different drag correlations used in CFD simulations. Results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.
Keywords: CFD; drag coefficient; solid suspension; solid-liquid velocities; UVP

Critical review of membrane bioreactor models - Part 2: Hydrodynamic and integrated models - Naessens, W.; Maere, T.; Ratkovich, N.; Vedantam, S.; Nopens, I. (Bioresource Technology, 2012)
Membrane bioreactor technology exists for a couple of decades, but has not yet overwhelmed the market due to some serious drawbacks of which operational cost due to fouling is the major contributor. Knowledge buildup and optimisation for such complex systems can heavily benefit from mathematical modelling. In this paper, the vast literature on hydrodynamic and integrated MBR modelling is critically reviewed. Hydrodynamic models are used at different scales and focus mainly on fouling and only little on system design/optimisation. Integrated models also focus on fouling although the ones including costs are leaning towards optimisation. Trends are discussed, knowledge gaps identified and interesting routes for further research suggested. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: CFD; Costs; hydrodynamics; Integrated model; Modelling

Crystallization: key thermodynamic, kinetic and hydrodynamic aspects - Vedantam, Sreepriya; Ranade, Vivek V. (Sadhana-Academy Proceedings in Engineering Sciences, 2013)
Crystallization is extensively used in different industrial applications, including the production of a wide range of materials such as fertilizers, detergents, food and pharmaceutical products, as well as in the mineral processing industries and treatment of waste effluents. In spite of the wide-spread use of crystallization, a clear understanding of the thermodynamic, kinetic and hydrodynamic aspects of the design methodologies are not yet well established. More often than not crystallization is still considered an art especially in fine-chemicals, pharmaceuticals and life-sciences sector. It is essential to understand and relate key thermodynamic, kinetic and hydrodynamic aspects to crystallizer performance, not just in terms of yield but also in terms of product quality (characterized by particle size distribution, morphology, polymorphism and the amount of strain as well as the uptake of solvent or impurities in the crystal lattice). This paper attempts to do that by critically reviewing published experimental and modelling studies on establishing and enhancing state-of-the-art thermodynamic, kinetic and hydrodynamic aspects of crystallization. Efforts are made to discuss and raise points for emerging modelling tools needed for a flexible design and operation of crystallizers and crystallization processes that are needed to meet the ever increasing demand on precise product specifications. Focus is on bringing out the trends which can be used as perspectives for future studies in this field.
Keywords: CFD; Crystallization; growth; Nucleation; polymorphism; supersaturation

Flow in vortex diodes - Pandare, Aditya; Ranade, Vivek V. (Chemical Engineering Research & Design, 2015)
A vortex diode is used as a cavitation device for treatment of industrial waste water and also, as a leaky non-return valve in nuclear applications. It consists of a vortex chamber with an axial and tangential port. When the fluid is injected through the tangential port, a strong vortex flow is set up in the diode chamber. This flow is characterized by phenomena such as vortex transition, precessing vortex core, toroidal recirculation zone, reverse flow core and recirculation zone in the axial port. Although studies have been conducted on the ``confined vortex'' class of flows (and some of them on vortex diodes), none of them provides a collective account of key nuances of the flow in a vortex diode. The flow in the diode differs from other confined-vortex flows on account of the axial-velocity deficit, due to which, direct correlations from other confined vortex flows cannot be applied to the diode. This work attempts to address the aforementioned flow characteristics in the diode using results primarily from CFD simulations. The reported methodology, computational model and results will be useful to gain better understanding of flows in vortex diodes and to optimize designs of vortex diodes for variety of applications. (C) 2015 Published by Elsevier B.V. on behalf of The Institution of Chemical Engineers.
Keywords: CFD; Confined vortex; Diode; Precessing vortex core; Recirculation

Two-phase flow boiling in 19mm tube: experiments and CFD modelling - Sardeshpande, Madhavi V.; Raymond, Barlev; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2016)
Boiling flows are encountered in a wide range of industrial applications such as boilers, nuclear reactors, electronic cooling, and various types of chemical reactors. Heat transfer coefficients, flow boiling regimes, flow instabilities, pressure drops, and conditions like dry-out are some of the key issues in every boiling flow study. It is observed that a limited experimental database is available for the 19mm ID channel diameter, i.e. a typical tube diameter of steam generator. Therefore, in the present work, the experimental setup was designed for studying boiling flows in a 19mm ID tube in such a way that different flow regimes occurring in a steam generator tube (from pre-heating of sub-cooled water to dry-out) could be investigated by varying inlet conditions. The reported results cover a reasonable range: 8-27kW/m(2) and 2.9-5.9kg/m(2)s heat and mass flux conditions, respectively. A basic computational flow model was also developed to facilitate interpretation of the obtained data. The presented design of the experimental setup and the approach of mimicking different types of steam generator tubes as well as presented experimental and simulated results are useful for gaining insight into complex boiling flows in tubes, and provide a sound basis for further work in this area.
Keywords: CFD; Flow regimes; two-phase flow boiling; vapour quality

Drying of almonds II: multiple particles - Chilka, A. G. (Indian Chemical Engineer, 2017)
Computational modelling is an efficient and effective tool for modelling the drying process for food products. Developing validated computational models for drying processes is essential to build energy-efficient drying units, producing uniform quality of dried products. This work presents drying behaviour of almonds with a specific focus on understanding interaction among multiple almonds. Eight (2 × 2 × 2) particles and twenty seven (3 × 3 × 3) particles arranged in the shape of a cuboid were used to conduct drying experiments in a Mettler Toledo Moisture Analyzer unit. Experiments were conducted to measure the moisture loss data with respect to drying time using almond kernels. Experimental data were used to understand drying kinetics as well as variation in moisture content with respect to their positions in a cuboid. Computational fluid dynamics based simulations were carried out for the flow, heat transfer and drying of particles in the unit. Actual geometry of individual particles was considered in simulations to predict the variation in velocity, heat and mass transfer coefficients for all the particles. Simulations predicted moisture loss data that matches well with the experimentally measured values. Average moisture for each layer was also compared for various intermediate drying times. Simulation results captured the overall drying process for multiple particles system adequately. The results are compared with the results obtained with drying of a single almond. The approach, models and presented results will be useful for designing large-scale drying units for almonds. © 2017 Indian Institute of Chemical Engineers
Keywords: Almonds; CFD; Drying

Estimation of gas induction in jet loop reactors: influence of nozzle designs - Sharma, D.V. (Chemical Engineering Research and Design, 2017)
Jet loop reactors are used widely for conducting gas liquid reactions because of the high mass transfer achieved in the gas–liquid ejector. Studies have shown that the mass transfer has a very strong correlation to the amount of gas induced in the ejector, and hence it is important to understand gas induction to enhance the performance of any gas–liquid nozzle. In this work, we used a single phase CFD model of the ejector with one adjustable parameter for estimating gas induction rates. After establishing that the model adequately describes the experimental data, the model was used for a quick evaluation of ejector geometries. Influence of key geometric parameters of gas–liquid ejectors like nozzle diameter, mixing tube length, distance between the nozzle outlet and mixing tube, suction chamber geometry and diffuser angle was investigated. It was found that dependence of gas induction on geometric parameters like distance between nozzle—mixing tube, suction chamber geometry, diffuser angle was either weak or had a clear maxima at or beyond a certain value of the geometric parameter. Other parameters like mixing tube length and nozzle diameter have a more complex impact on gas induction. The presented approach and results will be useful for quantifying influence of nozzle designs on gas induction rate in jet loop reactors.
Keywords: CFD; Gas Induction; Jet Loop Reactors; Nozzle Geometry

Pressure equalization approach for flow uniformity in microreactor with parallel channels - Madane, Ketan; Kulkarni, Amol A. (Chemical Engineering Science, 2018)
Numbering-up using parallel channels helps to achieve higher processing capacity while retaining the advantages of microreactors. However it may also lead to non-uniformity in flow across all the channels. Here we report the CFD simulations and experimental observations on the extent of uniformity in the flow from an assembly of several parallel channels. In the conventional parallel channel geometry, smaller channel size (<300 m) as well as higher fluid viscosity is seen to give better flow uniformity. Inequality in pressure distribution at the inlet of a large number of parallel channels is overcome by having two `pressure equalization slots' at an equal distance from inlet and outlets that open in the respective manifolds. Having such an arrangement helped to reduce the standard deviation in the flow by almost 90% when compared to the conventional geometry. However the modification was seen to increase the extent of back mixing to some extent. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: CFD; Experiments; Flow distribution; microreactor; Numbering-up; Parallel channels

Antisolvent based precipitation: batch, capillary flow reactor and impinging jet reactor - Pal, Sayan; Madane, Ketan; Kulkarni, Amol A. (Chemical Engineering Journal, 2019)
A method for continuous antisolvent precipitation of ammonium perchlorate (AP) using a confined impinging jet reactor (CIJR) is studied. The geometry of the CIJR was optimized to achieve excellent mixing with a significant reduction in the particle deposition on walls. Initially, the experimental conditions were optimized in a batch system and then in a continuous capillary reactor. Later those conditions extended for antisolvent precipitation of AP in an impinging jet reactor using water and n-butyl alcohol as a solvent and antisolvent, respectively for optimum performance. The performance was compared with the experiments in batch mode as well as and in a continuous capillary reactor. Over a range of inlet jet velocity that corresponded to 1792 < Re < 7193 for the saturated aqueous solution of AP and 1135 < Re < 4553 for the antisolvent butanol phase, 8.98-16.98 mu m Ammonium perchlorate particles were attained.
Keywords: Ammonium perchlorate; Antisolvent precipitation; CFD; continuous flow; Impinging jet reactor; microparticles

CFD modelling of almond drying in a tray dryer - Chilka, Amarvir G.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2019)
Drying is important in many food processing applications, and particularly so in the dry fruits industry. This work is focused on developing computational models for simulating the drying of almonds in a tray dryer. It is important to quantitatively understand heat and mass transfer within and around a single almond particle as well as the particle-particle interactions and their implications for dryer design. In this work, we have developed a systematic CFD modelling framework for modelling almond drying in a tray dryer. A single tray filled with almonds (similar to 2 kg) were dried at three set temperatures viz., 55, 65, and 75 degrees C. Air relative humidity at the inlet and outlet locations, and the weight of almonds were measured during drying for each experiment. An additional set of experiments were conducted in which almonds were filled only in the half section of the tray, keeping the other half empty. The same amount of almonds were used, to have multiple layers of almonds in the tray, and the set temperature for the experiment was 75 degrees C. Flow, heat, and mass transfer in the tray dryer were simulated using commercial CFD software Ansys Fluent. The validated computational model was used to simulate various cases including larger and more trays. The developed approach and models will be useful to select the appropriate dryer configuration and optimize its design. The developed models will also be useful to identify suitable operation conditions for the drying of almonds as well as other food products.
Keywords: Almonds; CFD; Drying; scale-up; tray dryer

Flow, mixing, and heat transfer in fluidic oscillators - Khalde, Chirag M.; Pandit, Ajinkya V.; Sangwai, Jitendra S.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2019)
There is an increasing emphasis on process intensification and development of compact, intensified reactors and separators in recent years. Significant efforts are being made to develop such intensified reactors and separators without any moving parts. Some of the recent research studies have proven that a liquid-liquid extractor based on the Coanda effect and feedback oscillations exhibit excellent mixing and liquid-liquid contacting. These fluidic oscillators can potentially be used for a variety of other multiphase reactions and systems demanding enhanced mixing and heat and mass transfer. In this work, we have computationally investigated flow, mixing, and heat transfer in fluidic oscillators based on the Coanda effect. Available information on flow and mixing in fluidic oscillators was critically reviewed and key gaps in the available knowledge with respect to the design and optimization of fluidic oscillators were identified. Computational flow models were developed to characterize key flow features like unsteady flows, secondary vortices, and internal recirculation over a range of Reynolds number (Re = 90-1538) for three different oscillator designs. Systematic numerical studies were carried out to quantify different flow regimes, oscillations, and the influence of key geometric parameters on flow, mixing, and heat transfer. Simulated results were critically analyzed and are presented in the form of dimensionless numbers. The approach and results presented in this work will provide useful insights and a systematic basis for extending the applications of the Coanda-based feedback oscillatory devices for a wide range of engineering applications.
Keywords: CFD; Coanda effect; fluidic oscillators; heat transfer; mixing